Research on the Status Quo and Countermeasures of Resident Waste Classification in Hefei City - Xu, Yaqi; Azam, S. M. Ferdous; Tham, Jacquline (International Journal of Natural Resources and Environmental Studies, 2024)
With the acceleration of economic development and urbanisation, the amount of waste in cities around the world has surged, and Hefei City is also facing pressure on waste management. Between 2018 and 2024, Hefei City has achieved remarkable results by promoting the policy of residential waste classification through three phases, including policy initiation, deepening promotion and consolidation and optimisation. However, there are still problems such as low awareness of residents’ classification, insufficient facilities, outdated technology and ineffective supervision. For this reason, it is recommended to strengthen publicity and education, improve facilities, enhance technology, strengthen supervision and promote multi-party co-operation. By optimising the measures, it will promote the in-depth development of waste classification and management in Hefei, improve resource utilisation and promote the development of the circular economy.